1993
DOI: 10.1038/364798a0
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking the tumour necrosis factor receptor 1 are resistant to IMF-mediated toxicity but highly susceptible to infection by Listeria monocytogenes

Abstract: Tumour necrosis factor (TNF), jointly referring to TNF alpha and TNF beta, is a central mediator of immune and inflammatory responses; its activities are mediated by two distinct receptors, TNFR1 (p55) and TNFR2 (p75) (reviewed in refs 1-3). The cytoplasmic domains of the TNFRs are unrelated, suggesting that they link to different intracellular signalling pathways. Although most TNF responses have been assigned to one or the other of the TNF receptors (mostly TNFR1), there is no generally accepted model for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
757
5
11

Year Published

1996
1996
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,201 publications
(804 citation statements)
references
References 28 publications
28
757
5
11
Order By: Relevance
“…Previous studies have also suggested that TNF- § in combination with or without IFN-+ plays an important role in activating resident macrophages to kill intracellular pathogens such as L. monocytogenes and T. gondii [4, [38][39][40][41][42]. However, no correlation was observed between the increase of resistance and in vitro TNF- § production in this study (Fig.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Previous studies have also suggested that TNF- § in combination with or without IFN-+ plays an important role in activating resident macrophages to kill intracellular pathogens such as L. monocytogenes and T. gondii [4, [38][39][40][41][42]. However, no correlation was observed between the increase of resistance and in vitro TNF- § production in this study (Fig.…”
Section: Discussioncontrasting
confidence: 57%
“…5D, left panel). Besides IFN-+ , other cytokines such as TNF- § have also been proposed to be an important factor in resistance to intracellular pathogens [4, [38][39][40][41][42]. However, in contrast to IFN-+ , substantial levels of TNF- § were produced by + c -/-(y) -Rag-2 -/-splenocytes with or without exogenous APC fractions in response to L. monocytogenes, and no apparent correlation was observed between the amounts of TNF- § and the susceptibility to L. monocytogenes (Fig.…”
Section: Adoptive Transfer Of Ifn-q -Producing Apc Provides Resistancmentioning
confidence: 99%
“…Only low [37], and it has been previously shown that the ensuing lethality is TNF-dependent and requires p55 TNF receptor signaling [38,39]. To analyze the respective phenotype of the generated mutant mice, Tnf +/+ , Tnf -/-and Tnf tm/tm mice were challenged with bacterial LPS/D-gal.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies addressed the critical role of WT or memTNF D1-9,K11E and of TNF receptors in antibacterial host defenses [31,38,39,43,44]. To determine the role of mutant tmTNF D1-12 protein in host defense mechanisms we measured the survival of Tnf +/+ , Tnf -/-and Tnf tm/tm mice following challenge with a high and a low dose of Listeria monocytogenes (LM).…”
Section: Tmtnf Supports Host Defenses Against Listeria Monocytogenes mentioning
confidence: 99%
“…2 TNF knockout mice showed that TNF is essential in resistance to infectious disease. 3 That these findings were relevant to human autoimmune/inflammatory diseases is evidenced by the high efficacy of anti-TNF antibodies (Infliximab) and recombinant soluble chimeric receptor in treating rheumatoid arthritis (RA) and Crohn's disease. 4,5 More recently, their significance was further highlighted in human infectious disease, when the observation was made that in patients treated with Infliximab, reactivation and a severe course of tuberculosis is strongly over-represented 6 These latter findings indicate an important role for TNF in controlling M. tuberculosis and most probably other intracellular infections in humans.…”
Section: Introductionmentioning
confidence: 99%